Natural Monuments: Mount Etna’s Chestnut Trees - Rosario Scaduto (Agathón)
The article addresses the importance of ancient tree crops in the Italian landscape. It dwells on the need for a long-standing census on knowledge, preservation and promotion of these trees and quotes some of the current Italian laws. Finally, the essay focuses on Mount Etna’s Chestnut trees, natural wonder monuments which have marvelled travellers of the 18th century and still continue to amaze and touch.